Solve for y -15=-2y+5(y-6)

Math
-15=-2y+5(y-6)
Rewrite the equation as -2y+5(y-6)=-15.
-2y+5(y-6)=-15
Simplify -2y+5(y-6).
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
-2y+5y+5⋅-6=-15
Multiply 5 by -6.
-2y+5y-30=-15
-2y+5y-30=-15
Add -2y and 5y.
3y-30=-15
3y-30=-15
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Add 30 to both sides of the equation.
3y=-15+30
Add -15 and 30.
3y=15
3y=15
Divide each term by 3 and simplify.
Tap for more steps…
Divide each term in 3y=15 by 3.
3y3=153
Cancel the common factor of 3.
Tap for more steps…
Cancel the common factor.
3y3=153
Divide y by 1.
y=153
y=153
Divide 15 by 3.
y=5
y=5
Solve for y -15=-2y+5(y-6)

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top